2020
DOI: 10.1097/jfn.0000000000000285
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Workplace Violence Toward Nursing Students in Iran: A Qualitative Study

Abstract: Background and Aims: This study explores the dimensions of violence experienced by student nurses in Iran, during their nurse education. The incidence of violence toward students has become a major concern and strategies are needed to reduce the incidence.Methods: A qualitative study was conducted. Participants were 7 male and 9 female third-year undergraduates nursing student. Purposive sampling was used and qualitative data from semi-structured interviews were analyzed using thematic content analysis.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…The identified issues were grouped into three subthemes including: Organisational which included the clinical educational and patient environment or culture (Hallett et al, 2021; Lash et al, 2006; Smith et al, 2016; Tee & Valiee, 2020; Thomas et al, 2015; Üzar‐Özçetin et al, 2021; Warshawski, 2021). The second subtheme was Aspects related to staff(ing) which included staff's lack of knowledge about the educational needs of RNS (Amoo et al, 2021; Hallett et al, 2021; Rafati et al, 2017; Smith et al, 2016; Tee & Valiee, 2020), specific staff personalities (Ahn & Choi, 2019; Anthony & Yastik, 2011; Birks et al, 2017; Courtney‐Pratt et al, 2018; Hallett et al, 2021; Smith et al, 2016; Thomas et al, 2015; Üzar‐Özçetin et al, 2021) and workload stress (Amoo et al, 2021; Rafati et al, 2017; Thomas et al, 2015). The final subtheme was Registered Nurse students' characteristics which encapsulated a lack of confidence, unbalanced power dynamics, and inherent vulnerability (Courtney‐Pratt et al, 2018; Kim et al, 2018; Lash et al, 2006; Rafati et al, 2017; Smith et al, 2016; Tee et al, 2016; Thomas et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The identified issues were grouped into three subthemes including: Organisational which included the clinical educational and patient environment or culture (Hallett et al, 2021; Lash et al, 2006; Smith et al, 2016; Tee & Valiee, 2020; Thomas et al, 2015; Üzar‐Özçetin et al, 2021; Warshawski, 2021). The second subtheme was Aspects related to staff(ing) which included staff's lack of knowledge about the educational needs of RNS (Amoo et al, 2021; Hallett et al, 2021; Rafati et al, 2017; Smith et al, 2016; Tee & Valiee, 2020), specific staff personalities (Ahn & Choi, 2019; Anthony & Yastik, 2011; Birks et al, 2017; Courtney‐Pratt et al, 2018; Hallett et al, 2021; Smith et al, 2016; Thomas et al, 2015; Üzar‐Özçetin et al, 2021) and workload stress (Amoo et al, 2021; Rafati et al, 2017; Thomas et al, 2015). The final subtheme was Registered Nurse students' characteristics which encapsulated a lack of confidence, unbalanced power dynamics, and inherent vulnerability (Courtney‐Pratt et al, 2018; Kim et al, 2018; Lash et al, 2006; Rafati et al, 2017; Smith et al, 2016; Tee et al, 2016; Thomas et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This, in turn, might have decreased the tendency to violence among the latter students. [6][7][8] The concept of care, which is essential and indispensable for the profession of nursing, is the basic nursing paradigm that aims to improve the health status and well-being of patients. 28,31 The analysis of the relationship between the gender and caring behavior of the nursing students in our study showed that both the female and male participants obtained high scores from the CBI-24, but the female participants obtained significantly higher scores than their male counterparts (p = 0.001; Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this finding, we may suggest that the junior students and the students, who lived with their parents, felt more stressed and responsible whereas the students, who lived in dormitories, had lower level of stress, thanks to the support of their friends. This, in turn, might have decreased the tendency to violence among the latter students 6–8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations